Performance evaluation of WC-12wt%Co as grinding wheel abrasive material by machining a titanium alloy - Enever, Anton Alexander (Stellenbosch : Stellenbosch University, 2016)
ENGLISH ABSTRACT: Grinding has been the most common machining process for material removal in manufacturing for many decades. The process originated from the realization that harder materials have the ability to abrasively alter the geometry and surface finish of softer materials. It was originally used in construction of buildings by abrasively forming limestone building bricks into desired shapes and sizes. This process has evolved over time to the high precision manufacturing industries of the modern era. High quality and high precision parts are manufactured with the use of grinding wheels, from rough part forming or part cutting to precision automotive engine components such as cam shafts. Most abrasives in modern grinding processes have been developed for general applications, while others are intended for specialised applications. The use of tungsten carbide as abrasive for both general and specialised grinding wheels is not generally implemented in industrial applications or used in published research work. This carbide falls in the refractory group of materials. When it is mixed and sintered with a ductile metal such as cobalt, molybdenum or nickel, its classification changes to a cemented carbide or cermet (ceramic metal). The amount of metal incorporated in a cermet mainly influences the ductility and transverse rupture strength. A metal content of about 12 wt% (12 weight %) is roughly the midway between a hard and brittle and a ductile cermet, giving tungsten carbide a unique hardness to ductile ratio. The metal that works best with tungsten carbide is cobalt, thus producing the cermet WC-12wt%Co. This specific cermet is commonly used as the base material for machining tools (for lathes and milling machines) due to its high hardness to toughness ratio that is needed for machining hard metals such as tool steels or titanium alloys. The base WC-12wt%Co material can be used as is for machining, but it is commonly coated with layers of other high wear resistant materials (such as titanium nitride, TiN, or titanium carbo-nitride, TiCN). This study focuses on the custom manufacture of a grinding wheel containing WC-12wt%Co as abrasive material, bonded together by an epoxy resin binder. This type of grinding wheel is not in use in industrial applications and must thus be specially designed and produced. The resin is used as binder, which is the case for many industrially implemented grinding wheels, to ease the production process and make it safer. The grinding wheels that were produced in this study are the smaller variant called mounted points. The performance of these mounted points was determined by the grinding of a titanium alloy and measuring the rate of wear, the surface finish the points produce on the titanium alloy and the surface hardness of the alloy.